Ландшафти Волинської області - Міщенко, Олена Віталіївна; Mishchenko, Olena V. (Тернопільський національний педагогічний університет імені Володимира Гнатюка, 2016)
Волинська область розташована в межах двох ландшафтних зон: мішаних лісів і широколистяних лісів. Основними фізико-географічними особливостями ландшафтів області Волинського Полісся є наявність крейдових порід, рівнинність, значний розвиток льодовикових форм рельєфу, карсту, високе залягання ґрунтових вод, розвинута річкова мережа, заозереність, перезволоженість і заболоченість, широкий розвиток долинних ландшафтів. Ландшафти Волинської височинної області характеризуються як рівнинні та горбисті природно-територіальні комплекси, які виникли серед широколистяних і хвойно-широколистяних лісів де, крейдові відклади, перекриті суцільним плащем лесових утворень на яких сформувались ґрунти чорноземного типу під трав’яною рослинністю та сірі опідзолені під широколистяними, дубово-грабовими лісами.

Volyn region is located within two landscape zones: mixed forests, which distinguish the region Volyn Polesia and deciduous forests, which formed Volyn highland region. The boundary between the natural areas is the line where the water-glacial sands and the loamy sands, border with the loess loam and the loamy sands. There are four levels in the spatial distribution of natural landscapes of Volyn region: the floodplain meadows and marshes, the fluvial terraces, the slopes without terraces, the tops of loess strands. The major physiographic features of the landscape area of Volyn Polesia are the presence of Cretaceous rocks, plainness, the significant development of glacial landforms, karst, a high occurrence of groundwater, significant density of river network and lakes, high moisture and a lot of swamps, a lot of lowland landscapes. The intense transformation of the landscapes of Volyn Polesia is caused by the development of the transport network, drainage of woodlands soils, extensive agricultural works, reducing the forest areas. However, processes such as forming of the swamps and wetlands, karst sometimes hinder the development of human activities in the area. The landscapes of Volyn highland region are flat and hilly nature-territorial complexes arising among deciduous and coniferous-deciduous forests, where Cretaceous sediments are overlain by a solid mantle of loess formations on which were formed chernozem type of soils covered with herbaceous vegetation and grey podzol soils covered with oak and hornbeam forests. One of the main factors of anthropogenic landscapes transformation of Volyn highland region is relatively high occupancy and cultivation. The temperate climate and hydrological regime of the most fertile soils in the region have contributed to a continuous intensive tillage of partitioned upland landscapes of Volyn region and forming of ravine and beam shapes.
The landscapes of Volyn region
Keywords: природний ландшафт; фізико-географічне районування Волинської області; господарське використання ландшафтів; область Волинського Полісся; Волинська височинна область; natural landscape; physical-geographical regionalization of the Volyn region; economic use of the landscape; the region of Volyn Polesia; Volyn highland region